Analysis of the mRNAs in spores of Bacillus subtilis - Korza, George; Nagler, Katja (Journal of bacteriology, 2019)
Large-scale shotgun sequencing (RNA-seq) analysis of mRNAs in dormant Bacillus subtilis spores prepared on plates or in liquid generally found the same ∼46 abundant mRNA species, with >250 mRNAs detected at much lower abundances. Knowledge of the amount of phosphate in a single B. subtilis spore allowed calculation of the amount of mRNA in an individual spore as ∼106 nucleotides (nt). Given the levels of abundant spore mRNAs compared to those of other mRNAs, it was calculated that the great majority of low-abundance mRNAs are present in only small fractions of spores in populations. Almost all of the most abundant spore mRNAs are encoded by genes expressed late in sporulation in the developing spore under the control of the forespore-specific RNA polymerase sigma factor, σG, and most of the encoded proteins are in spores. Levels of the most abundant spore mRNAs were also relatively stable for a week at 4°C after spore harvest. RNA-seq analysis of mRNAs in highly purified and less-well-purified spores made in liquid, as well as from spores that were chemically decoated to remove possible contaminating mRNA, indicated that low-abundance mRNAs in spores were not contaminants in purified spore preparations, and several sources of low-abundance mRNAs in spores are suggested. The function of at least the great majority of spore mRNAs seems most likely to be the generation of ribonucleotides for new RNA synthesis by their degradation early in spore revival.IMPORTANCE Previous work indicates that dormant Bacillus subtilis spores have many hundreds of mRNAs, some of which are suggested to play roles in spores' "return to life" or revival. The present work finds only ∼46 mRNAs at ≥1 molecule spore, with others in only fractions of spores in populations, often very small fractions. Less-abundant spore mRNAs are not contaminants in spore preparations, but how spores accumulate them is not clear. Almost all abundant spore mRNAs are synthesized in the developing spore late in its development, most encode proteins in spores, and abundant mRNAs in spores are relatively stable at 4°C. These findings will have a major impact on thinking about the roles that spore mRNAs may play in spore revival.
Gesehen am 28.05.2019